Dynamics of Democracy in Indonesia: A Literature Review of the Role of Political Parties in Democratic Consolidation - Samsidar, Samsidar (Journal of Politica Governo, 2025)
This study aims to analyze the role of political parties in the consolidation of democracy in Indonesia through a qualitative approach with a literature study method. The political transition after the 1998 reform has opened up a more open democratic space, but has not yet fully produced substantive democracy. Political parties as the main pillars of democracy should carry out the functions of interest aggregation, political education, cadre formation, and supervision of the government. However, various literatures show that political parties in Indonesia still face various challenges, such as oligarchic dominance, weak internal democracy, low quality of cadre recruitment, and a tendency towards political pragmatism. This study uses secondary data from journal articles, academic books, and reports from credible institutions which are systematically analyzed using content analysis techniques. The results of the study show that political parties have not been able to become effective agents of democratic consolidation due to the lack of party institutionalization and low political literacy of the community. Therefore, a comprehensive reform of the party system is needed through institutional strengthening, internal transparency, and encouragement of more inclusive political participation. This study provides a conceptual understanding of the institutional obstacles to Indonesia's democratization and recommends strategic steps to realize democracy that is not only procedural, but also substantive and sustaina